Assessment of prelinguistic vocalizations in real time: a comparison with phonetic transcription and assessment of inter-coder-reliability - Willadsen, Elisabeth; Persson, Christina; Patrick, Kathryn; Lohmander, Anette; Oller, D. Kimbrough (Clinical linguistics & phonetics, 2020)
This study investigated reliability of naturalistic listening in real time (NLRT) compared to phonetic transcription. Speech pathology students with brief training in NLRT assessed prelinguistic syllable inventory size and specific syllable types in typically developing infants. A second study also examined inter-coder reliability for canonical babbling, canonical babbling ratio and presence of oral stops in syllable inventory of infants with cleft palate, by means of NLRT. In study 1, ten students independently assessed prelinguistic samples of five 12-month-old typically developing infants using NLRT and phonetic transcription. Coders assessed syllable inventory size as more than twice as large using phonetic transcription as NLRT. Results showed a strong correlation between NLRT and phonetic transcription (syllables with more than five occurrences) for syllable inventory size (r = .60; p < .001). The methods showed similar results for inter-coder reliability of specific syllable types. In study 2, three other students assessed prelinguistic samples of twenty-eight 12-month-old infants with cleft palate by means of NLRT. Results revealed perfect inter-coder agreement for presence/absence of canonical babbling, strong correlations between the three coders' assessment of syllable inventory size (average r = .83; p < .001), but more inter-coder variability for agreement of specific syllable types. In conclusion, NLRT is a reliable method for assessing prelinguistic measures in infants with and without cleft palate with inter-coder agreement levels comparable to phonetic transcription for specific syllable types.